Climbing the Ladder: An Authentic Leadership Program Boosting Adolescent Girls’ Potential. - Manuel M. Molina-López; Susana González-Pérez; M. Carmen García-Centeno; Miryam Martínez-Martínez (SAGE Open)
This study explores the realm of authentic leadership theory to examine how female teenagers can enhance relational authenticity and develop authentic leadership skills through a specialized program. Employing multigroup Structural Equation Modeling (SEM), we assess the impact of this leadership intervention on female teenagers, comparing pre- and post-intervention results. Additionally, we contrasted the outcomes of program participants with those of same-aged, non-participating students from similar backgrounds. The analysis revealed a significant increase in the scores for the four constructs of authentic leadership among the program’s participants. Notably, their academic grades also improved post-intervention. Focusing on high school females aged 16 years and above, the study addresses a critical age for developing self-perception of competence and confidence. The persistent underrepresentation of females in leadership roles underscores the necessity for early interventions like this one. These findings contribute to a deeper understanding of how a leadership program can positively influence the development of authentic leadership skills among participants, while also observing enhancements in academic achievement following this particular intervention